Weed Community in Soybean Responses to Agricultural Management Systems - Edita Stefanic; Sanda Rasic; Pavo Lucic; Snjezana Tolic; Dinko Zima; Slavica Antunovic; Božica Japundžić-Palenkić; Ivan Stefanic (Agronomy, 2022)
Weed infestation is a major cause of the poor yield of soybeans (Glycine max (L.) Merr.); therefore, proper weed management represents one of the most important and expensive steps in soybean production. Field experiments were established in northeastern parts of Croatia, in the Vukovar-Syrmia county from 2014 to 2016, arranged in a split-plot design with four replications. Two different studies were conducted: the first study was to determine the weed interference, weed biomass accumulation, yield, and yield components of soybeans growing in three different rows spacing (25, 50, and 70 cm), and the second study aimed to simulate a risk analysis by building models of probabilities for generating profit as a result of weed control. The weed community in soybean during the study period comprised 34 dicot and grass species of a varied perennation. Compositional differences in the weed community tended to be affected most by the year (humid–arid environment), followed by row spacing. There were no differences in the weed biomass accumulation with a reduction in row spacing from 70 to 50 and 25 cm. The dominant weed species Amaranthus retroflexus, Ambrosia artemisiifolia, Chenopodium album, Datura stramonium, Setaria viridis, and Sorghum halepense formed the main biomass and were spread over all row spacings. There was a significant influence of row spacing, the duration of weed interference, and year on soybean yield and yield components. Weed infestation until the second trifoliate (V2) stage had no detrimental effect on soybean yield, regardless of the row spacing. The number of pods per plant significantly decreased at the same V2 stage in 25 and 50-cm rows, but in 70-cm soybean rows, this process started later, at four unfolded trifoliate leaves (V4 stage). A 1000 kernel weight was less sensitive to weed infestation and was significantly decreased at full flowering (R2 stage) in 25 and 70 cm rows, while it already decreased at the V4 stage in 50 cm rows. The probability distribution of achieving a profit showed the best results for soybeans growing in 70 cm rows, with preemergence herbicide application and two inter-row cultivation.